Dense integration of chlorocatechols crosslinked polyphenylene sulfide solid-state separator for Li metal-free batteries - Haitao Zhou; Lianlu Wan; Jiacheng Han; Jian-Chun Wu; Yihong Deng; Jie Gu; Huanggang Wang; Hongquan Gao; Zilong Su (Chemical Engineering Journal Advances)
Dry electrode film fabrication technology, known for its environmental friendliness and low energy consumption, is recognized as an effective industrial approach for producing highly dense solid-state electrolytes and pore-free separators. It holds promise for applying thin lithium metal and Li metal-free anodes in ultra-high energy density Li-ions batteries. However, the films produced by this method suffer from issues such as poor toughness, low strength, uneven thickness, and difficulties in rewinding, which limit its widespread adoption in the large-scale manufacturing of lithium batteries. In this study, we propose a hydrothermal process to introduce a chlorocatechol-based cross-linker onto the surface of highly crystalline polyphenylene sulfide (PPS) powder. By employing the dry electrode process, a PPS-based solid-state separator (PPS-SSS) is fabricated, featuring a thin profile (18±2 μm), a smoother surface, and a denser structure, significantly enhancing its mechanical properties. Moreover, the dense integration structure and chlorocatechol groups contribute to a higher Li+ transference number and more effectively inhibit the growth of Li dendrites. Li metal-free batteries, constructed with this separator, a Sn-plated Cu 10 μm foil anode, and a thick high-nickel cathode dry electrode, exhibit high discharge areal and specific capacities (5 mAh cm−2 and 200 mAh g−1, respectively) and pouch battery device energy density exceeding 440 Wh kg−1. Impressively, even in the presence of Cu or Fe powder contamination on the CuSn foil anode or cathode, this separator can still achieve uniform electric field distribution and lithium deposition, demonstrating good cycle stability.